Key MRI Features in Acute Stroke: Insights from an MRI-First Approach at a Tertiary Care Centre - Ahmad Sobri Muda (Journal Of Cardiovascular, Neurovascular & Stroke, 2024)
Magnetic Resonance Imaging (MRI) has emerged as a crucial tool in acute stroke management, offering superior sensitivity and specificity in detecting early ischemic changes. This review explores key MRI features in acute stroke based on insights from an MRI-first approach implemented at Universiti Putra Malaysia's tertiary care center. The Putra Acute Stroke Protocol, an optimized 8-minute MRI protocol, has demonstrated the feasibility of prioritizing MRI in hyperacute stroke settings. The manuscript discusses essential MRI sequences, including Diffusion-Weighted Imaging (DWI), Fluid-Attenuated Inversion Recovery (FLAIR), and Susceptibility-Weighted Imaging (SWI). It highlights the diagnostic and prognostic significance of specific imaging markers such as the FLAIR Vascular Hyperintensity Sign (FVHS), Susceptibility Vessel Sign (SVS), and Prominent Vein Sign (PVS). These features provide crucial information about infarct core, penumbra, collateral circulation, and thrombus composition, guiding treatment decisions and improving patient outcomes. The review also addresses the challenges and benefits of implementing an MRI-first policy, including concerns about delays and costs, while emphasizing its value in personalizing stroke management. By leveraging MRI's capabilities, clinicians can make more informed decisions about reperfusion therapies, potentially extending treatment windows for suitable candidates and improving overall stroke care.